An Interview with Anthony C.K. Kakooza, J.D., Ph.D. - Sara Benson; Siyao Cheng; Anthony Kakooza (Journal of Copyright in Education and Librarianship)
In this insightful interview, Anthony Kakooza engages in a comprehensive exploration of legal frameworks and their intersection with traditional cultural expressions (TCEs). The dialogue, facilitated by Sara R. Benson and Siyao Cheng from the Journal of Copyright in Education and Librarianship (JCEL), delves into a nuanced analysis of the role that copyright law plays in protecting TCEs. The conversation extends to encompass a wide array of topics related to the ongoing debates surrounding TCEs. Specifically, Kakooza addresses the prevalent misunderstandings associated with TCEs and sheds light on the intricate challenges posed by a regional framework for TCE protections. Furthermore, the conversation navigates to the merits of the sui generis approach to TCE protection and explores the implications of adopting a legal framework for indigenous communities and their TCEs. Drawing on Kakooza’s educational background and field experience, the interview serves as a valuable reference for readers aiming to grasp the complex dynamics between legal mechanisms and the protection of TCEs.